(adsbygoogle = window.adsbygoogle || []).push({}); Use binomial theorem to prove

C(n,0) - 3(C(n,1)) + 9(C(n,2) - 27(C(n,3) + ... + (-3)^n(C(n,n) = (-2)^n

From looking at the data given b = (-3) so a = 1 so (-2)^n = (1-3)^n

With this I know the equation in sigma notation and could probably prove the theorem through mathematical induction but I'm not certain that is what they are looking for in this case....

Update:

I proved n=1 and assumed n = k, so do I need to prove n= k+1 through mathematical induction?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Use binomial theorem to prove

**Physics Forums | Science Articles, Homework Help, Discussion**